Screening and fermentation characteristics of superior indigenous Saccharomyces cerevisiae from table grapes in the eastern foothills of Helan Mountain - ZHAO Haixia, WANG Xiaolei, ZHANG Xiu (Zhongguo niangzao)
By comparing fermentation power, ethanol production capacity and tolerance tests, the superior indigenous Saccharomyces cerevisiae were screened from the skins and natural fermentation mash of table grapes from the eastern foothills of Helan Mountain in Ningxia, and the screened strains were identified by molecular biology. The physicochemical indexes and volatile aroma substances of Cabernet Sauvignon dry red wine prepared by the screened strains were analyzed by conventional analysis method and GC-MS, and the cluster analysis (CA) was carried out based on the results. The results showed that 2 indigenous yeast strains Y7 and Y28 with fast fermentation speed, high yield of ethanol, tolerance of ethanol volume fraction 18%, glucose 400 g/L, SO2 350 mg/L and pH 2.0 were selected and identified as S. cerevisiae. Compared with commercial S. cerevisiae XR, there was no significant difference in the alcohol content, total acid, total SO2, free SO2 and pH of wine samples fermented by strains Y7 and Y28 (P>0.05). The volatile acid content of wine sample fermented by strain Y7 was the highest (0.36 g/L). A total of 48 volatile aroma compounds were detected in the Cabernet Sauvignon dry red wine samples, mainly esters and alcohols. The cluster analysis (CA) results showed that there were differences in the aroma characteristics of wine samples fermented by strains Y7 and Y28 compared with commercial S. cerevisiae XR. The strains Y7 and Y28 had certain potential to brew wines with characteristics of the producing region.